The roles of women in contemporary terrorism: Perpetrators, victims or something else? - Đorić Marija (Srpska Politička Misao)
The author analyzes all the roles that women can play in modern terrorism. Until now, science has mostly focused on the role of women as perpetrators and victims in terrorist activities. However, the author also pays special attention to the third role of a woman, which has not been sufficiently investigated so far - as a mothers. Viewing the role of women as mothers in terrorism has a dual character: while on the one hand, mothers can play a significant role in the prevention of terrorism (especially with sons), on the other hand they can also encourage their children in terms of terrorist activities, especially if they are and radicalized ones. The author gives a series of examples that specifically concern Islamist terrorism and the role of the mother in preventing or encouraging this phenomenon. The role of a woman as a mother has not been explored to a large extent in other forms of terrorism, which would represent a significant contribution for future scientific research. Also, this role of the mother is mainly related to certain so-called conservative regions, such as the Balkans or the Middle East, where the role of the mother is specific, especially in the upbringing of male children. Numerous prejudices are a complicating factor in elaborating the role of women in terrorism. One of them is that women are exclusively members of the "gentler" and "weaker" sex, and that as such they cannot be linked to terrorism. Another prejudice that is rooted in human society concerns the gender relationship to politics. Namely, since ancient Greece, politics was explicitly seen as a public job and a "male activity", while women were reserved for the oikos, as a private sphere. Hence, terrorism as a political phenomenon is mostly seen as a "male phenomenon." The subject of the research is directed towards different ideologies of terrorism, which condition accordingly, and different approaches towards women. The author points out that just as terrorism does not know race, religion and nation, it does not know gender either, and that attention should also be paid to the gender dimension when researching this phenomenon.